ANALISIS SINTAKSIS FUNGSI KALIMAT IMPERATIF BAHASA BATAK DALAM FILM “NGERI-NGERI SEDAP KARYA BENE DION RAJAGUKGUK SEBAGAI ALTERNATIF BAHAN AJAR - Putri Khoirunnisa; Dindin M.Z.M; Musaddad Abdul Aziz (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was conducted to provide solutions to the problems experienced by teachers. One of them is in determining the right teaching materials to be used by students so that they are interesting and not boring. In addition, students who have difficulty in writing review texts are also a problem. This research is expected to be able to provide solutions to problems in determining teaching materials and in accordance with the study of review texts at MTs Matlaul Anwar Dahu Pandeglang. The purpose of this study was to analyze the syntax of the imperative sentence functions of the Batak language in the film "Ngeri-Ngeri Sedap" by Bene Dion Rajaguguk as an alternative to teaching materials for review texts in class VIII MTs Matlaul Anwar Dahu Pandeglang. The results of the syntactic analysis of the function of imperative sentences in the film "Ngeri-Ngeri Sedap" by Bene Dion Rajagukguk contain 3 types of imperative sentences including, 66 sentences showing strong imperative sentences in the form of "function of giving instructions" totaling 10 sentences, "function of commanding" totaling 18 sentences , "function to warn" as many as 26 sentences, "function to threaten" as many as 12 sentences. 53 sentences showing neutral imperative sentences in the form of "function of giving advice" of 13 sentences, "function of giving advice" of 8 sentences, "function of giving permission" of 1 sentence, "function of reminding" of 14 sentences, "function of entertaining" of 11 sentences , "function shows politeness" as many as 6 sentences. 17 sentences showing weak imperative sentences in the form of "function of expressing requests" of 9 sentences, "function of begging" of 5 sentences, "function of begging" of 3 sentences. The results of this analysis are then used as an alternative teaching material for class VIII MTs Matlaul Anwar Dahu Pandeglang review text.